Biogas production from algal biomass: A review. (March 2015) - Montingelli, M.E.; Tedesco, S.; Olabi, A.G.
Abstract: The objective of this work is to provide a comprehensive study on algal biomass as feedstock for biogas production. Algae-derived biofuels are seen as one of the most promising solutions to mitigate climate change and as alternative to fast depleting of fossil fuels and oil reserves. Microalgae and macroalgae underwent an intense academic and industrial research, thanks to their capability to overcome the drawbacks related to the first and second generations of biomass resources. Major advantages of algae are: no competition with food crops for arable land, high growth rates, low fractions of lignin which reduces the need for energy-intensive pretreatment and compatibility with biorefinery approach implementation. However, some disadvantages such as the presence of high water content, seasonal chemical composition and the occurrence of inhibitory phenomena during anaerobic digestion, make algal biofuels not yet economically feasible although they are more environment friendly than fossil fuels.